2017
DOI: 10.14257/ijbsbt.2016.8.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Using Probabilistic Classification Technique and Statistical Features for Brain Magnetic Resonance Imaging (MRI) Classification: An Application of AI Technique in Bio-Science

Abstract: There are many medical imaging modalities used for the analysis and cure of various diseases. One of the most important of these modalities is Magnetic Resonance Imaging (MRI). MRI is advantageous over other modalities due to its high spatial resolution and the excellent capability of discrimination of soft tissues. In this paper, an automated classification approach of normal and pathological MRI is proposed. The proposed model three simple stages; preprocessing, feature extraction and classification. Two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…For this, we have applied the convolutional neural network for brain MRI classification. There are many classifiers, such as support vector machine, k-nearest neighbor, artificial neural network, random forest, and we have applied these classifiers in our previous studies [24,42,67]. However, a convolutional neural network performs the best in the sense of accuracy in this study.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…For this, we have applied the convolutional neural network for brain MRI classification. There are many classifiers, such as support vector machine, k-nearest neighbor, artificial neural network, random forest, and we have applied these classifiers in our previous studies [24,42,67]. However, a convolutional neural network performs the best in the sense of accuracy in this study.…”
Section: Resultsmentioning
confidence: 87%
“…The overall accuracy of the results of the proposed method is determined by using the performance evaluation factors, such as Kappa statistics, which is a measurement metric that carried out the comparison of the observed accuracy with the expected accuracy. This is considered true positive (TP), which indicates the accurate prediction of the positive class, false positive (FP), which indicates the inaccurate prediction of the positive class [24,42]. The precision is a performance matric that uses TP and FP factors to define the degree of measurements given in Equation (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fayaz et al (2016) suggested a three stages approach for brain MRI classification and hence achieved high accuracy. Wahid et al (2016) suggested a method for identifying normal and abnormal MR images using three stages such as preprocessing, feature extraction and then apply probabilistic classifier and obtained high accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%